Spatial differentiation of gully clusters based on the regional scale: an example from northeastern China - Zhao,Ying; Zhang,Bin; Qin,Wei; Luo,Jun; Liu,Hui; Deng,Qingchun; Lv,Wei; He,Yuli; Wang,Houling (PeerJ, 2020)
Gully erosion represents a serious environmental threat around the world, but their spatial distribution law are unclear at the regional scale. To quantitatively characterize the spatial distribution model of gullies and determine the regularity of regional differentiation, this paper used spatial analyst and statistics method to study the spatial distribution of gullies in 34 sample areas of northeastern China based on interpretations of high-resolution remote sensing images. The results showed that the kernel density could quantitatively describe the continuous spatial clustering of gullies. Gullies in northeastern China had the characteristics of a spatially unbalanced distribution at the scale of the sample area. The average kernel density of the 34 sample areas (Moran’s I was 0.43, P¡0.01P < 0.01) also indicated clustering distribution at the regional scale. The horizontal clustering characteristics of gullies exhibited an azonal distribution of being low values in the middle plain and high values on the three mountainous areas. The average kernel density in the southeastern part of the study area was highest (maximum value of 2.38). In the vertical direction, gullies were relatively undeveloped in low- and high-altitude areas, while middle-altitude areas were beneficial to the development of gullies. The effect of height differences on gully development was more significant than altitude. As the height difference increased, gullies tended to be more clustered, which can be expressed by a power function. The results of this study will not only help to understand the regional differentiation characteristics of gullies but will also provide a scientific reference for the study of spatial distribution of gullies in future.
Keywords: Gully; Spatial cluster; Kernel density; Regional differentiation; Azonality